Component-wise application migration in bidimensional cross-cloud environments - Carrasco Mora, José Manuel; Durán, Francisco; Pimentel-Sánchez, Ernesto (ScitePress, 2017)
We propose an algorithm for the migration of cloud applications' components between different providers, possibly changing their service level between IaaS and PaaS. Our solution relies on three of the key ingredients of the trans-cloud approach: a unified API, agnostic topology descriptions, and mechanisms for the independent specification of providers. We show how our approach allows us to overcome some of the current interoperability and portability issues of cloud environments to propose a solution for migration, present an implementation of our proposed solution, and illustrate it with a case study and experimental results.
Keywords: Computación en nube; Cloud applications; Migration; Cross-cloud; Trans-cloud; Brooklyn; Standards; TOSCA